The role and importance of ecosystems in creating tourism activities - Štetić, Snežana; Trišić, Igor (Hotel and Tourism Management, 2018)
Tourism and forms that are manifested in a specific area are subjected to intensive scientific-professional analysis of different goals and tasks. In addition to monitoring the volume of tourism flow, it is also important to analyze the effects on ecosystem values within destinations. Such effects are mainly manifested on environmental elements such as air and water, but they are nothing less manifested on coastal areas, urban and mountain areas. All these effects are analyzed in this paper. Attractive tourism areas are also valuable biocoenosis which is inhabited with endemic plant and animal species. Besides that, those are the areas with fragile ecosystems, swamps, areas important for the protection of biodiversity, where ecological niche and valence are the priority in environment protection systems.